PENGARUH KONSENTRASI DAN WAKTU APLIKASI PUPUK ORGANIK CAIR LIMBAH PASAR TERHADAP HASIL SELADA (Lactuca sativa L.) - Syahrani, Syahrani; Darmi, Darmi; Riscal, Muhammad (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2015)
This research aims to determine the effect of the origin of the waste liquid organic fertilizer market and applicaton time on result lettuce. This research began in May to July 2013, located behind the office BP3K Muara Jawa Sub district, Kutai Kartanegara Regency, East Borneo Province.This research was arranged using a Randomized Complete Block Design (RCBD) 3 x 4 factorial with 3 (three) replication. As the first factor is the concentration of POC with 4 levels that are p0= without treatment (control), p1= 2,5 ml POC-1 liters of water, p2= 5,0 ml POC-1 liters of water, p3= 7,5 ml POC-1 liters of water. And the second factor is the treatment time of POC applications with 3 levels that are w1= fertilizer 3 days, w2= fertilizer 7 days, w1= fertilizer 10 days.Concentration and origin of the waste liquid organic fertilizer market is not a real effect on the average plant fresh weight. Results of plant fresh weight was highest at p3 concentration effect is 52,19 g.Liquid organic fertilizer application time origin does not affect the real market waste on average plant fresh weight. The results ofthe highest plant fresh weight at the time the application is w1 is 47,02 g.Interaction between the origin of the waste liquihd organic fertilizer market and application time did not significantly affect the average plant fresh weight. Fresh weight of the plants on the interaction effect of concentration and time of application is p3w3 that 57,09 g.Key word : result, lettuce, the waste liquid organic fertilizer market, applicaton time